An over-expression system for characterizing Ppt1 function in Drosophila - Korey, Christopher A (BioMed Central, 2003)
BACKGROUND: The infantile onset form of Neuronal Ceroid Lipofuscinoses (INCL) is the earliest and most severe form of NCL, with neurological symptoms that reflect massive neurodegeneration in the CNS and retina. INCL is due to recessively inherited mutations at the CLN1 locus. This locus encodes the evolutionarily conserved enzyme palmitoyl-protein thioesterase 1 (PPT1), indicating an essential role for protein palmitoylation in normal neuronal function. RESULTS: To begin to elucidate the specific role that Ppt1 plays in neuronal cells, we have developed a Ppt1 over-expression system in Drosophila. We report that over-expression of DmPpt1 in the developing Drosophila visual system leads to the loss of cells through apoptotic cell death. This DmPpt1 over-expression phenotype is suppressed by DmPpt1 genomic deficiencies. Moreover, over-expression of DmPpt1S123A, which bears a catalytic site serine 123 to alanine mutation, does not lead to the severe eye phenotype observed with over-expression of wild-type DmPpt1. Thus, cell loss in DmPpt1 flies is directly related to the dosage of wildtype DmPpt1. CONCLUSIONS: Although INCL is due to the loss of PPT1; increased levels of DmPpt1 also lead to neurodegeneration possibly via a detrimental effect on some aspect of PPT1's normal function. This suggests that the precise levels of PPT1 activity are important for neuronal cell survival. The Drosophila DmPpt1 over-expression system provides a resource for genetic experiments that aim to identify the processes by which PPT1 regulates the palmitoylation-state of its essential protein substrates.